"Representative bureaucracy as a leadership issue: the Canadian case". Issue 4 (8th September 2020) - Mau, Tim A.
Abstract : Purpose: The public administration literature on representative bureaucracy identifies several advantages from having a diverse public service workforce, but it has not explicitly focused on leadership. For its part, the public sector leadership literature has largely ignored the issue of gender. The purpose of this paper is to rectify these limitations by advancing the argument that having a representative bureaucracy is fundamentally a leadership issue. Moreover, it assesses the extent to which representativeness has been achieved in the Canadian federal public service. Design/methodology/approach: The paper begins with a discussion of the importance of a representative bureaucracy for democratic governance. In the next section, the case is made that representativeness is fundamentally intertwined with the concept of administrative leadership. Then, the article provides an interpretive case study analysis of the federal public service in Canada, which is the global leader in terms of women's representation in public service leadership positions. Findings: The initial breakthrough for gender representation in the Canadian federal public service was 1995. From that point onward, the proportion of women in the core public administration exceeded workforce availability. However, women continued to be modestly under-represented among the senior leadership cadre throughout the early 2000s. The watershed moment for gender representation in the federal public service was 2011 when the number of women in the executive group exceeded workforce availability for the first time. Significant progress toward greater representativeness in the other target groups has also been made but ongoing vigilance is required. Research limitations/implications: The study only determines the passive representation of women in the Public Service of Canada and is not able to comment on the extent to which women are substantively represented in federal policy outcomes. Originality/value: The paper traces the Canadian federal government's progress toward achieving gender representation over time, while commenting on the extent to which the public service reflects broader diversity. In doing so, it explicitly links representation to leadership, which the existing literature fails to do, by arguing that effective administrative leadership is contingent upon having a diverse public service. Moreover, it highlights the importance of gender for public sector leadership, which hitherto has been neglected.